RP-HPLC Method Development and Validation for Determination of Abemaciclib in Bulk Drug Substance and Pharmaceutical Dosage Forms - Maithani, M.; Dwivedi, D.K. (Journal of Biomedical and Pharmaceutical Research, 2023)
A simple, economic, rapid and precise method for the quantification of Abemaciclib in bulk drug substance and pharmaceutical dosage forms was developed and validated using RP-HPLC. The chromatographic separation was achieved using Ascentis® C-18 HPLC column (250mm x 4.6mm i.d., particle size 5µ) with mobile phase containing 0.5% TFA: methanol: acetonitrile (35:45:20 v/v/v) with flow rate of 1.2mL/ min was used and effluents were monitored at 295nm. The retention time of Abemaciclib were found to be 3.72 min. The linearity was in the range of 6-42μg/mL. The limit of detection and limit of quantification were found to be 0.6 and 1.8 µg/mL, respectively. The % recoveries were found to be in the range of 99.65±0.77. Keywords: Abemaciclib, Estimation, Bulk drug substance, Pharmaceutical dosage forms